GMPPB-Associated Dystroglycanopathy: Emerging Common Variants with Phenotype Correlation - Jensen, Braden S. (Hum Mutat, 2015)
Mutations in GDP-mannose pyrophosphorylase B (GMPPB), a catalyst for the formation of the sugar donor GDP-mannose, were recently identified as a cause of muscular dystrophy resulting from abnormal glycosylation of α-dystroglycan. In this series, we report nine unrelated individuals with GMPPB-associated dystroglycanopathy. The most mildly affected subject has normal strength at twenty-five years, while three severely affected children presented in infancy with intellectual disability and epilepsy. Muscle biopsies of all subjects are dystrophic with abnormal immunostaining for glycosylated α-dystroglycan. This cohort, together with previously published cases, allows preliminary genotype-phenotype correlations to be made for the emerging GMPPB common variants c.79G>C (p.D27H) and c.860G>A (p.R287Q). We observe that c.79G>C (p.D27H) is associated with a mild limb-girdle muscular dystrophy phenotype, while c.860G>A (p.R287Q) is associated with a relatively severe congenital muscular dystrophy typically involving brain development. Sixty-six percent of GMPPB families to date have one of these common variants.